Serological evaluation of an influenza A virus cold-adapted reassortant live vaccine, CR-37 (H1N1), in Japanese adult volunteers. - Yamane, N. (Cambridge University Press, 1984)
A cold-adapted influenza A virus, CR-37 (H1N1), derived from genetic reassortment between A/Ann Arbor/6/60 (H2N2) cold-adapted variant virus and A/California/10/78 (H1N1) wild-type virus, was tested in Japanese adult volunteer. The CR-37 live virus preparation induced only low-grade clinical reactions in volunteers for the first 3-4 days after inoculation. Two vaccinees who did not show any antibody changes became febrile (over 38.0 degrees C). Skin tests using the vaccine preparation and uninfected allantoic fluid were performed, and indicated that one of these two vaccines was positive for the CR-37 vaccine preparation. A high proportion of the vaccinees whose sera had a haemagglutination-inhibition (HI) antibody titre against the vaccine strain of less than or equal to 64 before inoculation, seroconverted in both HI and neuraminidase-inhibition (NAI) antibody titrations, and only a few seroconverted in the titration of antibody against type-specific internal antigens. The serological examinations against heterotypic H1N1 variants indicated that the cold-adapted live influenza virus vaccine could induce a broad spectrum of HI antibody reactivity and immunity of long duration.